FARM LABORERS TOWARDS THE MIDDLE CLASS: THE AMAK AWAK GROUP IN NAGARI LABUAH GUNUANG KEC. LAREH SAGO HALABAN, WEST SUMATRA 1980-2015 - Yuhasnil, Yuhasnil; Hazmi, Nahdatul; Asmara, Dedi (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2024)
The emergence of farm laborers in Nagari Labuah Gunuang has been going on since early 1949. Their presence was related to the lack of agricultural production, which affected the economic survival of their families. From 1960 to 1966, the survival of the laborers' families was tested again. Women who were previously engaged in the domestic sector, then shared work with their husbands by doing labor. The method used in this research is the historical method which consists of heuristics (data collection), source criticism, interpretation, and historiography. The purpose of this research is to see the activities and influence of the Amak Awak group in family resilience. The results of the research obtained that the women's labor group formed since 1980, then legalized as Amak Awak (2011) had an impact on the economic conditions of their families. They initially only worked in the agricultural sector, but also in animal husbandry. In fact, from their labor activities, they were able to buy 1 hectare of land, which they cultivated and enjoyed the results for the common good. They are no longer in the lower class, but have entered the middle class.